Adsorption Using Biochar from Palm Oil Empty Fruit Bunches for Advanced Treatment of Palm Oil Mill Secondary Effluent - Elsa Windiastuti; S. Suprihatin; Nastiti Siswi Indrasti; Yazid Bindar; Udin Hasanudin (Journal of Applied Science and Engineering, 2025)
Biochar can be produced from empty oil palm fruit bunches (EFB) through a pyrolysis process. The biochar can be considered as a low-cost adsorbent for advanced processing of palm oil mill secondary effluent (POMSE). This research aims to evaluate the efficiency of adsorption using EFB biochar in advanced treatment of the electrocoagulation treated POMSE. Biochar activation was carried out through pretreatment and post-treatment. No combination of pretreatment and post-treatment of biochar was carried out. The adsorption process was carried out using EFB biochar at doses of 0, 40, 80, and 120 g/L, and contact times of 1, 3, and 5 hours. The adsorbate used was POMSE which had undergone an electrocoagulation process at a voltage of 15 volts for 30 minutes. The research results showed that the adsorption with the EFB biochar was able to reduce COD by 82.29-95.74%, turbidity by 74.96-93.89% and color by 19.67-46.45%. The results of SEM-EDX analysis shown an increase in nutrients and minerals content in the used biochar. The elements content of C, O, K, Ca, Al, and Mg in the biochar that was used for adsorption were 44.81%, 21.53%, 13.89%, 16.41%, 0.47% and 2.88%, respectively. The BET surface area of post-treatment biochar was 24.1982 m2/g. Adsorption with post-treatment biochar at a dose of 40 g/L with a contact time of 1 hour was the best treatment in this study. It is possible to be used as organic fertilizer or soil improver for agricultural application. At the same time, its application could act as a carbon sink to reduce carbon emissions from the palm oil industry.